2011
DOI: 10.1111/j.1750-2659.2011.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

Influenza neuraminidase

Abstract: Influenza neuraminidase is the target of two licensed antivirals that have been very successful, with several more in development. However, neuraminidase has been largely ignored as a vaccine target despite evidence that inclusion of neuraminidase in the subunit vaccine gives increased protection. This article describes current knowledge on the structure, enzyme activity and antigenic significance of neuraminidase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
218
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(220 citation statements)
references
References 102 publications
2
218
0
Order By: Relevance
“…However, the structural and functional roles of the stalk domain of NA were unknown thus far, and there was no report about the glycosylation of these canonical glycosites (19)(20)(21)(22)(23). In this study, we prove that the glycosites in the stalk domain of NA are glycosylated to regulate the activity, affinity, and specificity of NA to modulate IAV replication, suggesting that the glycans in the stalk domain of NA play an important role in the virulence and transmission of IAV.…”
Section: Discussionmentioning
confidence: 51%
“…However, the structural and functional roles of the stalk domain of NA were unknown thus far, and there was no report about the glycosylation of these canonical glycosites (19)(20)(21)(22)(23). In this study, we prove that the glycosites in the stalk domain of NA are glycosylated to regulate the activity, affinity, and specificity of NA to modulate IAV replication, suggesting that the glycans in the stalk domain of NA play an important role in the virulence and transmission of IAV.…”
Section: Discussionmentioning
confidence: 51%
“…5). Although the GCN4-extended HN and VN proteins differed dramatically in their K m values and in their specific activity, none of these residues belong to the active site or framework residues (16)(17)(18) (Fig. 5 and 6).…”
Section: Construction and Expression Of Recombinant Na Proteinsmentioning
confidence: 99%
“…Each blade is formed by four anti-parallel beta sheets, which are stabilized by disulfide bonds and connected by loops of various lengths. The active site of NA is composed of highly conserved catalytic and structural residues that either directly contact the SIA substrate or hold the catalytic residues in place (16)(17)(18). Tetramerization of the NA protein is important for the formation of the active site and synthesis of active enzymes (19).…”
mentioning
confidence: 99%
“…1A). The RNA-tag was inserted into the region of the NA gene that encodes the NA stalk (12). Analysis of wild-type and recombinant viruses revealed that virus growth was unaffected by the presence of the RNA tag ( Fig.…”
Section: Significancementioning
confidence: 99%